ANALISIS KINERJA KEUANGAN PADA RSUD DAYAKU RAJA KOTA BANGUN KABUPATEN KUTAI KARTANEGARA - MUHAMMAD IQBAL; YANA ULFAH; IRWANSYAH - (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2016)
The purpose of this study to analyze the financial performance of hospital Dayaku Raja in 2014 and 2015, in terms of liquiditas ratio, solvency ratio, and debt ratio. Based on the analysis using the liquidity ratio, current ratio and cash ratio increased from the previous years. The increase in this ratio indicates the performance of hospital dayaku raja good, because the hospital is able to pay its current liabilities. While the quick ratio decreasedfrom the prioryear due to supply by 2015 is greater than 2014 but still considered healthy. From the analysis using solvency ratio show that the financial performance of hospitals dayaku raja is in a secure position for total assets greater than total liabilities. Based on the analysis using the debt ratio, debt to equity ratio and the ratio of debt to capital assets have increased from the previous year. It shows the financial performance of hospitals dayaku raja either because it is not burneded by debt.Keywords: Liquidity Ratio, Solvency Ratio, and Debt Ratio.